2017
DOI: 10.1111/cmi.12715
|View full text |Cite
|
Sign up to set email alerts
|

Expression dynamics and physiologically relevant functional study of STEVOR in asexual stages ofPlasmodium falciparuminfection

Abstract: The extensive modification of Plasmodium falciparum-infected erythrocytes by variant surface antigens plays a major role in immune evasion and malaria-induced pathology. Here, using high-resolution microscopy, we visualize the spatio-temporal expression dynamics of STEVOR, an important variant surface antigens family, in a stage-dependent manner. We demonstrate that it is exported to the cell surface where protein molecules cluster and preferentially localize in proximity to knobs. Quantitative evidence from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
(138 reference statements)
1
11
0
Order By: Relevance
“…We analyzed four selected STEVOR proteins with highly similar transcriptional profiles using, to our knowledge for the first time, well-characterized STEVOR variant-specific antisera in conjunction with corresponding transgenic parasite lines. In agreement with numerous previous studies, we observed a localization of all variants at the erythrocyte membrane in trophozoite stages, underlining their putative function in cell-cell interactions (911, 13, 26, 54). Similar to our results, GFP-tagged STEVOR versions were previously shown to be retained at the Maurer’s clefts, indicating that the interaction of the STEVOR C terminus with the erythrocyte cytoskeleton (55) is hampered by GFP tagging and precludes transport to the IE membrane (15).…”
Section: Discussionsupporting
confidence: 93%
“…We analyzed four selected STEVOR proteins with highly similar transcriptional profiles using, to our knowledge for the first time, well-characterized STEVOR variant-specific antisera in conjunction with corresponding transgenic parasite lines. In agreement with numerous previous studies, we observed a localization of all variants at the erythrocyte membrane in trophozoite stages, underlining their putative function in cell-cell interactions (911, 13, 26, 54). Similar to our results, GFP-tagged STEVOR versions were previously shown to be retained at the Maurer’s clefts, indicating that the interaction of the STEVOR C terminus with the erythrocyte cytoskeleton (55) is hampered by GFP tagging and precludes transport to the IE membrane (15).…”
Section: Discussionsupporting
confidence: 93%
“…This process involves the adhesion of parasite-exported proteins, known as ligands, expressed on the infected RBC (iRBC) membrane to receptors on host cells 3 . iRBCs can either bind to endothelial cells 7 , form rosettes with uninfected RBCs 8 , 9 , or cluster amongst themselves via platelet interactions 10 . Sequestered iRBCs occlude microvasculature 11 , 12 , induce the release of damaging inflammatory mediators 13 , and cause disruptions to host metabolism 14 .…”
Section: Introductionmentioning
confidence: 99%
“…STEVOR proteins have also been shown to be associated with the erythrocyte membrane in immature gametocytes stages (McRobert et al, 2004; Tiburcio et al, 2012). Although the adhesive domain of STEVOR was detected at the erythrocyte surface in asexual stages where it plays a role in rosetting (Niang et al, 2009; Niang et al, 2014; Singh et al, 2017; Wichers et al, 2019), recent immunofluorescence studies convincingly showed that this domain is not exposed at the surface of erythrocytes infected with immature gametocytes (Neveu et al, 2018). At the mature gametocyte stage, STEVOR proteins are no longer detectable at the erythrocyte membrane, probably as a result of conformational changes upon dephosphorylation (Tiburcio et al, 2012; Naissant et al, 2016; Figure 1B).…”
Section: Protein Export At the Erythrocyte Membranementioning
confidence: 99%